2023
DOI: 10.1177/23259671221148458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Double-Level Osteotomy Versus Open-Wedge High Tibial Osteotomy for Bifocal Varus Deformity

Abstract: Background: In bifocal varus deformity, double-level osteotomy (DLO) is advocated to treat lower limb alignment to prevent an adverse increase in joint line obliquity. Purpose/Hypothesis: The purpose of this study was to compare the clinical and radiological results after DLO and open-wedge high tibial osteotomy (OWHTO) in patients with combined varus deformity. It was hypothesized that DLO would improve clinical results without increasing the complication rate compared with OWHTO. Study Design: Cohort study; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Despite that DLO is a more complex procedure and potentially carries higher risks, a quick return to sports rate was demonstrated in this group. In a recent study, Abs et al reported that DLO yields better activity and patient satisfaction levels with a more physiologic joint line obliquity [2]. A similarly high satisfaction level following DLO was reported by Schroter et al [35].…”
Section: Discussionmentioning
confidence: 70%
“…Despite that DLO is a more complex procedure and potentially carries higher risks, a quick return to sports rate was demonstrated in this group. In a recent study, Abs et al reported that DLO yields better activity and patient satisfaction levels with a more physiologic joint line obliquity [2]. A similarly high satisfaction level following DLO was reported by Schroter et al [35].…”
Section: Discussionmentioning
confidence: 70%
“…Additional correction of the mLDFA may be required if further correction is needed [23]. Double‐level osteotomies provide reliable and equivalent clinical results in these patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases of substantial or bifocal deformities, a single‐level osteotomy may significantly increase the joint line obliquity (JLO) with resultant tibiofemoral subluxation, pressure distribution changes and excessive shear stresses on the articular cartilage [ 2 , 34 , 37 , 54 ]. In such cases, DLO is gaining popularity over single‐level knee osteotomy due to its merits in maintaining a more physiologic joint alignment and orientation with better clinical results [ 1 , 7 , 47 ] and comparable return to sports [ 6 , 12 ]. Nevertheless, DLO is a complex procedure, and accuracy is of the essence.…”
Section: Introductionmentioning
confidence: 99%